Applications of peptide-based systems in diagnosis of cancer and COVID-19 - Ehsan, Sumia (Kansas State University, 2022)
Early detection is critical in diagnosing any disease as it increases the chances of survival and saves a patient from experiencing severe symptoms and related treatments, especially in diseases like cancer and coronavirus. At the molecular level, these conditions are found to be associated with an altered expression of specific biomarkers (biological molecules indicative of normal behavior or abnormality in a physiological process or condition), such as proteases and arginases. As these biomarkers are present not only in the tissues but also in the blood and other body fluids, liquid biopsy can be conveniently performed to detect these disease-specific enzymes, reducing patient discomfort, and allowing for repeated tests over time to track the development of the disease and monitoring the progress of treatment. To target such biomarkers, the use of peptides as a targeting moiety is getting substantial attention from scientists because of the ease of synthesis, flexibility in structure and function, cost-effectiveness, high specificity and selectivity towards a receptor, and high biocompatibility. This work focuses on developing peptide-based detection platforms for the clinical diagnosis of cancer (specifically lung cancer) at its early stages and coronavirus disease via liquid biopsy. The design of biosensors consists of an enzyme-specific peptide sequence labeled with tetrakis-carboxyphenyl-porphyrin (TCPP) and explosion graphene core-shell attached to polyethylenimine (PEI, to link peptide via amide bond). These consensus peptide sequences act as substrates for the enzymes/proteases that are overexpressed in lung cancer and COVID-19 diseases, hence, measuring the activity of lung cancer and coronavirus protease and arginase biomarkers. These detection systems work on the principle of Förster resonance energy transfer, where the cleaving of consensus peptide sequence by relevant proteases results in the termination of the fluorescence quenching of TCPP by graphene. The increase in the fluorescence intensity of TCPP upon the termination of quenching is measured using a plate reader. Furthermore, we optimized the solid-phase peptide synthesis protocol to find a suitable set of conditions to get the maximum purity of synthetic peptides, as confirmed by ultra-performance liquid chromatography-mass spectrometry (UPLC-MS). Hence, the newly developed biosensors with ultrapure peptides are highly sensitive and can detect the overly expressed disease biomarkers using a conventional plate reader down to the sub-femtomolar level and can potentially be used in laboratories with limited resources without any compromise on efficiency and sensitivity.
Keywords: Peptides in biomedical application; Biosensors; Cancer and COVID-19/coronavirus detection; Graphene and nanoparticles; Optimization of solid-phase peptide synthesis; Ultra-performance liquid chromatography-mass spectrometry (UPLC-MS)